2018
DOI: 10.1111/vcp.12595
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for the activity of lactate dehydrogenase and its isoenzymes in the serum and cerebrospinal fluid of healthy canines

Abstract: Knowledge of the distribution and concentration of LD in the serum and CSF of healthy dogs will set the foundation for future studies of canine LD as a potentially clinically useful biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…A study in 2013 13 had inconclusive findings on whether CSF lactate concentrations are correlated with peripheral blood lactate concentrations. Others found that canine serum total lactate dehydrogenase values were almost seven times that of the CSF 22 . For all dogs in this study, the median CSF lactate concentration was 2.1 mmol/L, which was greater than the median peripheral venous blood lactate concentration of 1.6 mmol/L.…”
Section: Discussioncontrasting
confidence: 60%
“…A study in 2013 13 had inconclusive findings on whether CSF lactate concentrations are correlated with peripheral blood lactate concentrations. Others found that canine serum total lactate dehydrogenase values were almost seven times that of the CSF 22 . For all dogs in this study, the median CSF lactate concentration was 2.1 mmol/L, which was greater than the median peripheral venous blood lactate concentration of 1.6 mmol/L.…”
Section: Discussioncontrasting
confidence: 60%
“…Insignificant increase of serum cTnI in some of the presented breeds could be explained by chronic cardiac remodeling process with increased MMVD severity (Chan et al 2019). However, elevated CK and LDH levels may not only present with cardiac damage but also with several localized and systemic diseases (Aktas et al 1993;Bakirel and Gunes 2009;Kopanke et al 2018). Interestingly, the CRP was undetectable in MMVD dogs compared to healthy one as previously reported (Ljungvall et al 2010).…”
Section: Discussionmentioning
confidence: 66%
“…Financial and ethical constraints prohibited the inclusion of more dogs, and unfortunately, this meant that the study could have been underpowered, therefore potentially resulting in type II errors, for example when comparing urine creatinine and UPC between groups. However, while only 98 Greyhounds were included in the final analysis, this number compares favorably with many other veterinary studies that have established RIs 30‐32 …”
Section: Discussionmentioning
confidence: 83%
“…However, while only 98 Greyhounds were included in the final analysis, this number compares favorably with many other veterinary studies that have established RIs. [30][31][32] Analytes are potentially influenced by storage, but this is unlikely to have affected the result of this study. Although urine samples were refrigerated at 4°C for up to 72 hours before UPC analysis;…”
Section: Discussionmentioning
confidence: 99%